Fatigue Testing Approach Utilising Machining Cutting Forces and Fixture Design - Okenyi, V.; Afazov, S.; Mansfield, N.; Siegkas, Petros; Serjouei, A.; Bodaghi, M. (My University, 2024)
Background: Traditional fatigue testing methods can be expensive due to the need of specialised equipment for engineering materials and structures. Thus, a new fatigue testing approach utilising machining cutting forces to induce cyclic stresses, enabling fatigue life assessment of engineering materials and structures, has been developed. Objective: This research aims to develop and verify a new testing approach using machining processes to enable the fatigue life assessment of engineering materials and structures. This is achieved by the utilisation of machining-induced cutting forces to generate cyclic stresses into welded samples used in applications of wind turbine monopile structures. Methods: The methodology employes the development of a fixture encompassed with strain gauges and purposefully designed machining operations to mimic the cyclic stresses experienced in real applications. The machining-based fatigue testing approach was demonstrated on welded samples by replicating cyclic stresses of offshore wind turbine monopiles subject to in-service loads. Results: The results show that rapid fatigue testing of engineering materials and structures is possible by utilising existing machine tools and centres, which are widely accessible to industry. Cyclic stresses were induced in welded structural steel samples proving the concept of this method. Conclusion: This novel fatigue testing method showed that cyclic stresses can be induced by machining cutting forces to address real application needs. The key advantages are that this method can be quickly set up in industry, enabling fast fatigue testing that can lead to reduction of lead times for product and process development of industrial components.
Keywords: Cutting force; Cyclic stresses; Fatigue testing method; Machining